Air oxidation of pollutants on cathodic nickel@nickel oxide/graphite felt under room condition. (1st July 2019) - Zhai, Lin-Feng; Kong, Shi-Yu; Duan, Ming-Feng; Sun, Min
Abstract: Oxygen in air is an eco-friendly and economical oxidant, and catalytic air oxidation technology have a great potential to sustain effective wastewater treatment. Here we report a novel cathodic air oxidation process under the catalysis of a nickel@nickel oxide composite loaded on a porous graphite felt. Such a process demonstrates extensive and stable effectiveness in oxidizing a variety of dyes, pharmaceuticals and personal care products at high mineralization efficiencies under room condition. Mechanistic study indicates organic pollutants are oxidized by oxygen at cathodic nickel@nickel oxide/graphite felt through a non-free radical pathway, in which oxygen atom is transferred from oxygen molecule to organic molecules via lattice oxygen species in nickel oxide. The nickel oxide is reduced in the cathodic electric field, liberating and activating lattice oxygen species as the oxidizer of organic pollutants. Then, oxygen re-oxidizes nickel into nickel oxide to replenish lattice oxygen species. Such an oxygen activation pattern through nickel/nickel oxide redox cycle enables pollutant degradation at low energy cost, thus endowing the cathodic air oxidation process with a great potential in practical wastewater treatment. Highlights: Cost-effective cathodic air oxidation process is catalyzed by Ni@NiO redox cycle. Various dyes are totally mineralization at −0.8 V with low energy consumption. The process follows a surface-catalyzed non-radical pathway with O2 as oxidizer. Pollutants are oxidized by lattice oxygen in Ni@NiO which is replenished from O2 . Reduction of NiO in cathodic electric field activates lattice oxygen.